골외성 점액성 연골육종의 임상 결과 - 공창배(Chang-Bae Kong); 김경훈(Kyung Hoon Kim); 남희승(Hee Seung Nam); 송원석(Won-Seok Song); 고재수(Jae-Soo Koh); 조완형(Wan-Hyeong Cho) (The journal of the Korean Orthopaedic Association, 2022)
목적: 골외성 점액성 연골육종은 전체 연부 조직 종양 환자 중 약 3% 이내에서 발생하는 매우 희귀한 종양이다. 이 종양은 매우 느리게 자란다는 특징으로 잘 알려져 있다. 저자들은 원자력병원에서 경험한 골외성 점액성 연골육종 환자들의 임상 양상과 종양학적 결과에 대해 알아보고자 하였다. 대상 및 방법: 2008년 1월부터 2018년 12월까지 원자력병원에서 골외성 점액성 연골육종으로 진단된 이후 치료 받은 17명의 환자를 대상으로 하였다. 이들의 나이, 성별, 증상 발현 기간, 종양의 위치 및 크기, 병기, 자기공명영상, 병리 소견을 후향적으로 분석하였고, 국소 재발 및 원격 전이 발생 시간, 추시 기간 및 종양학적 결과를 분석하였다. 생존율 분석에는 Kaplan–Meier 생존율분석법을 이용하였다. 결과: 남자가 10예, 여자가 7예였으며, 평균 연령은 54세(31–79세)였다. 종양의 위치는 둔부가 5예, 대퇴부 4예, 슬관절부 3예, 족부 3예, 견관절부 1예, 배부가 1예였으며 종양의 평균 크기는 11.5 cm (2.2–23.2 cm)였다. American Joint Committee on Cancer 병기에 따른 진단시의 분류는 5예에서 II, 3예에서 IIIA, 3예에서 IIIB, 6예에서 IV였다. 국소 재발이 12예, 원격 전이가 15 예에서 발생했다. 국소 재발은 평균 8개월(2–23개월), 원격 전이는 평균 7개월(1–32개월)에서 관찰되었다. 골외성 점액성 연골육종 환자의 Kaplan–Meier법을 이용한 5년 전체 생존율은 73%±17%였으며, 2명의 환자가 골외성 점액성 연골육종으로 인해 사망하였다. 결론: 높은 국소 재발률과 원격 전이율에도 불구하고, 골외성 점액성 연골육종의 느린 성장 속도로 인해 환자의 장기 생존율은 상당히 좋은 것으로 확인되었다. Purpose: Extraskeletal myxoid chondrosarcoma (EMC) is an extremely rare malignant mesenchymal neoplasm, accounting for less than 3% of soft tissue sarcomas. This sarcoma is usually characterized by its indolent course. This study examined the clinical manifestations and oncologic outcomes of EMC. Materials and Methods: Seventeen patients diagnosed and treated for EMC between January 2008 and December 2018 were enrolled in this study. The cohort was then reviewed regarding age, gender, symptom onset, tumor location, magnetic resonance images, surgical margin, and pathologic diagnosis. The time to local recurrence and metastasis, follow-up duration, and the patients’ final status were analyzed. Results: The patients were comprised of 10 males and seven female patients with a mean age of 54 (range, 31–79). The tumor location was the buttock in five, thigh in four, knee in three, foot in three, shoulder in one, and back in one. The average tumor diameter was 11.5 cm (range, 2.2–23.2 cm). At the time of diagnosis, five patients were American Joint Committee on Cancer stage II; three were IIIA; three were IIIB; six were IV. Local recurrence occurred in 12 cases, and distant metastasis occurred in 15 cases. The five-year overall survival of the patients with EMC was 73%±17%, and two patients died of the disease. Conclusion: Despite the high rate of local recurrence and distant metastasis, the long-term survival rate in patients with EMC is quite high because of its indolent characteristics. KCI Citation Count: 0